2009
DOI: 10.1007/s00442-009-1301-5
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide alters habitat selection and aquatic community composition

Abstract: Anthropogenic chemical contamination is an important issue for conservation of aquatic ecosystems. While recent research highlights that community context can mediate the consequences of contaminant exposure, little is known about how contaminants themselves might determine this context by altering habitat selection and thus initial community composition. Here we show that the insecticide carbaryl and its commercial counterpart Sevin can affect aquatic community composition by differentially altering ovipositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…Our work also shares some elements with Vonesh and Kraus (2009) who reported that habitat selection and thus community structure were impacted by the presence of pesticides. Vonesh and Kraus (2009) make the point that habitat selection is not random yet this is often a default assumption in metapopulation models.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our work also shares some elements with Vonesh and Kraus (2009) who reported that habitat selection and thus community structure were impacted by the presence of pesticides. Vonesh and Kraus (2009) make the point that habitat selection is not random yet this is often a default assumption in metapopulation models.…”
Section: Discussionsupporting
confidence: 73%
“…Vonesh and Kraus (2009) make the point that habitat selection is not random yet this is often a default assumption in metapopulation models. Here we showed that leaving rates may differ among domiciles, but in a non-obvious manner that is driven by state dependence and the presence or absence of pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…[35]), but aquatic taxa may be susceptible to traps that arise in other ways (e.g. pollution [36]). A wider focus could allow the degree to which findings from particular studies might transfer to other sites and systems to be assessed, which is a key component of a general, predictive understanding of ecology [37].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research documents the negative impact of these chemicals on freshwater life (e.g., Whitton 1970;Forstner and Prosi 1979;Munn et al 2006;Vonesh and Kraus 2009), yet more recently road salt deicers have been identified as a rising source of salinization to freshwaters in the United States (Kaushal et al 2005). Freshwater salinization is becoming a year-round phenomenon due to long-term storage and transport of dissociated salt ions (e.g., chloride, sodium, magnesium) in groundwater and soils (Jackson and Jobbagy 2005;Howard and Maier 2007;Kelly et al 2008;Mullaney et al 2009).…”
Section: Introductionmentioning
confidence: 99%